2009
DOI: 10.1088/0953-8984/21/6/064249
|View full text |Cite
|
Sign up to set email alerts
|

A new structure of Cu complex in Si and its photoluminescence

Abstract: A recent discovery of complicated isotope shifts of the PL 1014 meV line in Cu-containing silicon, which was made by Thewalt's group, indicates that existing models of Cu pairs are not appropriate for accounting for the luminescence center. A new structural model has been studied. First-principles calculations show that the most probable form of the complex is a four-membered complex which is composed of a substitutional Cu associated with three neighboring interstitial Cu atoms. The symmetry is C(3v). The for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
19
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…The local symmetry of the complex is C 3v , which is consistent with the uniaxial stress experiment by Weber et al [2]. The further additional subpeak structures found for Γ 4 line are interpreted in terms of non-totally symmetric phonon mode of this complex, probably an E mode [9].…”
supporting
confidence: 88%
See 3 more Smart Citations
“…The local symmetry of the complex is C 3v , which is consistent with the uniaxial stress experiment by Weber et al [2]. The further additional subpeak structures found for Γ 4 line are interpreted in terms of non-totally symmetric phonon mode of this complex, probably an E mode [9].…”
supporting
confidence: 88%
“…To study this PL center, we have investigated the stable configuration of Cu complex by first-principles calculation [9]. It is shown that a fourmembered complex Cu (s) Cu (3i) is the most stable configuration; one substitutional Cu and three neighboring interstitial Cu's.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Recombination-free four-copper-atom complexes start dissociating at 150 C 24 releasing three Cu i þ ions and an unknown Cu DLA center, 25 which might be Cu s . 26,27 Nevertheless, as substitutional copper is recombination active, 2 any Cu s release would cause a lifetime decrease at 200 C instead of the observed lifetime increase. Correspondingly, any other Cu s formation at 200 C would cause a further lifetime decrease, such as Cu i þ reaction with a vacancy, 28 a silicon self-interstitial, 29 or an oxygenvacancy center.…”
mentioning
confidence: 98%